Wing phosphorylation is a major functional determinant of the Lrs14‐type biofilm and motility regulator AbfR1 in Sulfolobus acidocaldarius. Issue 5 (7th July 2017) - Li, Lingling; Banerjee, Ankan; Bischof, Lisa Franziska; Maklad, Hassan Ramadan; Hoffmann, Lena; Henche, Anna‐Lena; Veliz, Fabian; Bildl, Wolfgang; Schulte, Uwe; Orell, Alvaro; Essen, Lars‐Oliver; Peeters, Eveline; et al.
Summary: In response to a variety of environmental cues, prokaryotes can switch between a motile and a sessile, biofilm‐forming mode of growth. The regulatory mechanisms and signaling pathways underlying this switch are largely unknown in archaea but involve small winged helix‐turn‐helix DNA‐binding proteins of the archaea‐specific Lrs14 family. Here, we study the Lrs14 member AbfR1 of Sulfolobus acidocaldarius . Small‐angle X‐ray scattering data are presented, which are consistent with a model of dimeric AbfR1 in which dimerization occurs via an antiparallel coiled coil as suggested by homology modeling. Furthermore, solution structure data of AbfR1‐DNA complexes suggest that upon binding DNA, AbfR1 induces deformations in the DNA. The wing residues tyrosine 84 and serine 87, which are phosphorylated in vivo, are crucial to establish stable protein‐DNA contacts and their substitution with a negatively charged glutamate or aspartate residue inhibits formation of a nucleoprotein complex. Furthermore, mutation abrogates the cellular abundance and transcription regulatory function of AbfR1 and thus affects the resulting biofilm and motility phenotype of S. acidocaldarius . This work establishes a novel wHTH DNA‐binding mode for Lrs14‐like proteins and hints at an important role for protein phosphorylation as a signal transduction mechanism for the control of biofilm formation and motility in archaea. Abstract : The DNA‐binding protein AbfR1, which belongs to the archaea‐specific Lrs14 family, regulates biofilm formation in the crenarchaeon Sulfolobus acidocaldarius . In this work, we demonstrate that AbfR1 employs a novel wHTH DNA‐binding mode and that previously identified phosphorylation sites located on the wing are important for DNA binding. Their phosphorylation appears to influence the function of AbfR1 and thus, the regulation of biofilm formation and motility in S. acidocaldarius .